Domestic and foreign sovereign debt stability - Leonardo Barros Torres; Wojtek Paczos; Kirill Shakhnov (Cardiff University, Cardiff Business School, 2024)
We present a theory of determinants of sovereign debt stability on foreign and domestic markets. Besides the two traditional factors - debt size and output contractions, we highlight the role of the third factor: distortionary tax, which hinders the government's ability to freely raise revenues. We emphasise the impact of tax distortions and output fluctuations on the trade-off between domestic and foreign debt stability. The paper explains why outright defaults in domestic debt are rare, despite its significant share in public debt, and provides insights into optimal debt issuance and taxation strategies.
Keywords: F34; G15; H63; 330; sovereign debt; debt stability; selective default; debt composition; distortionary tax